Catalytic degradation of organic pollutants by manganese oxides: a comprehensive review. Issue 1 (31st December 2022) - Li, Hao; Fu, Bin; Huang, Hongying; Wu, Shuping; Ge, Jing; Zhang, Jing; Li, Feiyue; Qu, Ping
ABSTRACT: Manganese dioxide (MnO2 ) is a very promising catalyst material due to its unique physicochemical properties and synergistic effects with other metals or metal oxides. Especially, MnO2 was widely used to remove organic pollutants. In this paper, we summarize the phase and morphology structures of MnO2 . The effects of doping and composite on the structures and catalytic properties of MnO2 materials are also compared and described. The catalytic properties of MnO2 -based materials on organic pollutants (phenolic compounds, antibiotics, dyes, and pesticides) are also analyzed. In addition, we summarize the degradation mechanisms, degradation pathways, and degradation efficiency of different MnO2 -based materials on organic pollutants. The development status and shortcomings of MnO2 are discussed. Its development trend of catalytic degradation of organic pollutants by manganese oxides is provided.